(3JGQjN eSde GddMLis - (3eSde Hf eMeO Hf LYaQ GddMLj,J (B545 (3g` s
(3ChdgG (B:s
(3efge GdTQja GdbGVi eMeO Hf CMeO Hf Ydi Hf EHQGgje Hf GdeMSf GdYdhi hcGf ai eG HdZfi CMO abgGA GdRjOjI HGdjef hCMO YdeGFge s
(3BNQgG (B:s
(3abdJ CfG dYdi Hf jMji Ef eeG cGf eSWhQkG ai cJHg HCf GdHgGFe JHYK jhe GdbjGeI hJONd GdLfI hJfYe agh QCi HYV Cgd GdJfGSN Je hced s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B233s
Keywords: (3GdJGQjNs